Perbandingan Kemampuan Representasi Matematis Siswa Sekolah Dasar pada Penggunaan Media Pembelajaran Augmented Reality dan Pasir Kinetik - Nurbaiti Widyasari; Ismawati Ismawati (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2020)
This study aims to determine the difference of students’ representation ability through the Augmented Reality (AR) and kinetic sand as learning media. This research is a quasi-experimental by nonequivalent control group design. The students’ representation ability compared based on students’ prior mathematical ability (PMA) as high, medium, and low category. The data analyzed by using two path Anova on SPSS 16. The results of data analysis shown that there is no difference on students’ representation ability in both AR class and kinetic sand class in significance value of 0.68. In addition, there is no interaction between AR media and kinetic sand in significance value of 0.542.